Population dynamics of Capitella aff. teleta (Polychaeta, Capitellidae) in Gamo Lagoon, northeastern Japan, during a series of restoration works following the 2011 Great East Japan Earthquake and tsunami - Hashimoto, Akane; Sato-Okoshi, Waka (Frontiers in Marine Science, 2022)
The population dynamics of the capitellid polychaete Capitella aff. teleta were studied in Gamo Lagoon, located in northeast Japan, for the subsequent 2 years from 2016, when a series of restoration works was conducted following the 2011 Great East Japan Earthquake and tsunami. Capitella aff. teleta was found to be widely distributed from the estuary side, where the levee was located, to the innermost part but was more abundant in the innermost part, which is rich in organic matter. In the lagoon, the daily maximum water level dropped from 2017 to 2018 during the reconstruction of a flow-conducting levee, which blocked water flow and isolated the inner part of the lagoon. Although the density decreased drastically for approximately 11 months under diurnal hypoxia and strongly reducing conditions, small-sized new recruits were observed and the population recovered quickly after the daily maximum water level increased. In Gamo Lagoon, C. aff. teleta inhabiting the innermost part and estuary side of the lagoon contributed to maintaining the population by dispersing planktonic larvae between them. Thus, the maximum water level had a significant effect on the maintenance of the C. aff. teleta population in the lagoon, and sufficiently high water levels enable the dispersion of planktonic larvae to help recover the population quickly, suggesting that it is important to keep the water area connected.